Implementasi Program Pendidikan Inklusif di Kabupaten Bireuen - Ferizaldi Ferizaldi; Fazlina Fazlina (Asia-Pacific Journal of Public Policy, 2020)
The aim of National Education as stated in Law No. 20 of 2003 concerning the National Education System is to give all citizens the right to education, including those with physical, emotional, intellectual, mental, and/or social disabilities entitled to special education. This is also regulated in the Permendiknas R.I. Number 70 of 2009 concerning inclusive education. In this regard, the phenomenon of inclusive education in the Bireuen Regency is still not optimal. The results of this study indicate that the implementation of inclusive education in the Bireuen District encountered numerous barriers. From the aspect of human resources (i.e., teachers), almost all of them are not from an inclusive education background. Most teachers taught in inclusive schools are from the regular honorary teachers. Therefore, special teaching staff with a background in inclusive education are urgently required. Besides, the implementation of inclusive education programs in this region is not well-supported by the stakeholders. From the aspect of facilities and infrastructure, it is not sufficient or inadequate to support the implementation of inclusive education in this district.